1981
DOI: 10.3109/15563658108990264
|View full text |Cite
|
Sign up to set email alerts
|

An Exploratory Study of Manganese Exposure to Welders

Abstract: Sixty welders (20 each from Plants A, B, and C) and 20 control subjects were investigated for the possible occurrence of manganese poisoning among welders exposed to the welding fumes containing this metal. Ten, 9, and 5 welders from Plants B, C, and A, respectively, were diagnosed as suspected cases of early manganese poisoning. The diagnosis was based on the proof of overexposure to manganese by the findings of increased urinary levels of this metal, signs of early neurological involvement, and increased con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
33
0
2

Year Published

2001
2001
2016
2016

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 97 publications
(36 citation statements)
references
References 6 publications
1
33
0
2
Order By: Relevance
“…Our findings fit with others already noted in the scientific literature attesting to the release of manganese from welding activities causing neurologic damage, as well as a variety of other symptoms. This would include the work of Bowler [7], Chandra et al [16], Laohaudomchok et al [8], and Racette et al [9]. The finding in this study proves notable for the high rate of reported eye difficulties, even though most welders wear eye protection, albeit not very consistently.…”
Section: Short-term High Exposures (> 1 Mg/msupporting
confidence: 48%
“…Our findings fit with others already noted in the scientific literature attesting to the release of manganese from welding activities causing neurologic damage, as well as a variety of other symptoms. This would include the work of Bowler [7], Chandra et al [16], Laohaudomchok et al [8], and Racette et al [9]. The finding in this study proves notable for the high rate of reported eye difficulties, even though most welders wear eye protection, albeit not very consistently.…”
Section: Short-term High Exposures (> 1 Mg/msupporting
confidence: 48%
“…Cases of manganese intoxication among welders who chronically inhale airborne manganese emitted during the welding process have been documented in literature (Chandra et al, 1981;Mergler et al, 1994;Roels et al, 1987;Sjogren et al, 1996;Smargiassi et al, 2000). The shielded metal arc weld, which is the most commonly used form of arc weld, can generate the fume containing manganese as high as 28.4% weight of hazardous air pollutant (US-EPA, 1994).…”
Section: Introductionmentioning
confidence: 99%
“…However, cellular toxicity is an important drawback that challenges the applicability of Mn 2+ -enhanced MRI (MEMRI). It has been shown that Mn 2+ can be cytotoxic at concentrations used for neural tracing (Canals et al, 2008;Chandra et al, 1981;McMillan, 1999;Pal et al, 1999). Additional disadvantages of this technique are its high diffusion at the injection site, which challenge the specificity of the resulting projections, and its incompatibility with other visualization systems (Canals et al, 2008).…”
Section: Introductionmentioning
confidence: 99%